Analysis of Determining The Cost of Goods Produced in Determining The Selling Price of Msmes Cita Sport: English - Insani Zulfa; Darmo H. Suwiryo; Gatot Wahyu Nugroho (Muhasabatuna : Jurnal Akuntansi Syariah, 2023)
The main problem faced by MSME entrepreneurs is the determination of selling prices related to the cost of goods produced, this is the main problem in this study. With the aim of identifying and finding solutions in knowing the calculation of cost of goods produced, selling prices and cost of goods produced based on orders in determining selling prices at Cita Sport MSMEs. The method used in this study uses the company method and the job order costing method. The result of this study is that the calculation of cost of goods produced still uses a simple method that is changed to the job order costing method.